Identification of potent antibacterial inhibitors targeting methyltransferase Mtr1/TrmD in Haemophilus influenzae via molecular dynamics simulations - Saud Almawash; Sitah Alharthi (PLoS ONE, 2025)
Bacterial influenza is a significant global health and economic concern, and the effectiveness of current therapies is declining as bacterial resistance increases. This case emphasizes the need for novel therapeutic approaches. A target-based method was used in this study to investigate the RNA 2’-O-methyltransferase MTr1/TrmD, an important enzyme involved in the pathogenic bacteria’s cap-snatching mechanism. This post-translational modification is critical for bacterial pathogenicity, providing opportunities for the development of novel inhibitor compounds. Computational screening revealed numerous interesting small-molecule inhibitors that could efficiently limit MTr1 activity, resulting in antibacterial effects. Notably, Sinefungin, a recognized inhibitor, had a binding affinity of −7.2 kcal/mol, which was lower than the top three inhibitors tested: Molecule 45 (−8.7 kcal/mol), Molecule 55 (−8.5 kcal/mol), and Molecule 56 (−8.5 kcal/mol). Additional confirmation using molecular dynamics simulations indicated significant structural changes in the control-MTr1 complex, particularly at the transitions from loop to helix and helix to loop. The leading inhibitors, on the other hand, maintained stable connections with the active site residues throughout a 120 ns simulation. Binding free energy estimates (MM/PBSA and MM/GBSA), as well as water swap investigations, revealed that Molecule 56 had the highest binding affinity of the inhibitors studied. This is followed by waterswap analysis where the compound 56 remains the prominent one in terms of higher binding affinities. Hence, it has been found from computational studies that our inhibitors remain more static which will ease a way for experimentalists towards in vitro and in vivo studies. These findings indicate that the discovered compounds, particularly Molecule 56, have the potential for future in vitro and in vivo validation, paving the door for the development of novel antibacterial therapeutics against Haemophilus influenzae.